Potential distribution of Monotropa uniflora as a surrogate for range of Monotropoideae (Ericaceae) in South Asia - PRAKASH PRADHAN (Society for Indonesian Biodiversity, 2015)
Pradhan P. 2015. Potential distribution of Monotropa uniflora as a surrogate for range of Monotropoideae (Ericaceae) in South Asia. Biodiversitas 16: 109-115. Monotropoideae is a mycoheterotrophic subfamily of Ericaceae. Its members are highly specific to a particular fungal family, which has attributed to the rarity and limited distribution of Monotropoideae. In the past two decades, there are considerable developments in understanding their biology and biogeography, among which,the distribution of Monotropa uniflora L. and M. hypopitys L. has been extensively studied. In this contribution, Ecological Niche Modeling of M. uniflora has been conducted to test its earlier proposed distribution in South Asia, to test the spatial scale of the said proposal, to test its potential distribution as a surrogate for range of Monotropoideae in South Asia and to prioritize conservation areas for M. uniflora in the region. The model was built with five occurrence details of the rare plant M. uniflora in Western and Eastern Himalaya, in relation to 19 bioclimatic explanatory variables, performed in MaxEnt. The results show the good performance of the model with the training AUC of 0.994. 1,50,316 square Km. of suitable areas have been predicted for the growth of M. uniflora (IHS â‰¥0.5) in South Asia, many areas of which is in line with earlier distributional reports. The bioclimatic variables are able to predict and suitably justify the spatial distribution of M. uniflora. The predicted range of the species could be established for potential distribution of other Asian Monotropoids like Monotropastrum and Cheilotheca. Key words: Ecological Niche Modeling, Himalaya, MaxEnt, Mycoheterotrophy, Russulaceae